Evaluation of the In Vitro And In Vivo Antioxidant Potentials of Sudarshana Powder - Weerakoon, W.A.S.S.; Perera, P.K.; Gunasekera, D.; Suresh, T.S. (Proceedings of 9th International Research Conference, KDU, Sri Lanka, 8th - 9th Sept 2016, 2016)
Attached
Keywords: Antioxidant; Wistar rats; In-vitro and in-vivo